A Business History of the Swatch Group The Rebirth of Swiss Watchmaking and the Globalization of the Luxury Industry - Donzé, P. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book offers a detailed and full analysis of the strategy which enabled the Swatch Group to establish itself on the world market. In particular, it tackles the issues of production restructuring, with the opening of subsidiaries in Asia, and the implementation of a new marketing strategy, characterized by the move towards luxury.